The relationship between electricity consumption, trade, and GDP and the effect of COVID-19: a panel ARDL approach on the Visegrad countries - Uğurlu, Erginbay; Jindřichovská, Irena (Frontiers in Energy Research, 2024)
The aim of the study is to explore the linkage between electricity consumption, international trade and GDP during the COVID-19 pandemic in a sample of the Visegrad Four (V4) countries. The study uses data from the period of 2010 Q1–2021 Q3. Applying the panel-pooled mean group-autoregressive distributive lag (PMG-ARDL) model, we evaluate both long-run and short-run linkages among electricity consumption, trade, GDP, and the COVID-19 pandemic. We tested both the long-run and short-run linkages among electricity consumption, trade, GDP, and a COVID-19 dummy variable for the Visegrad countries. The main contribution of this study to the literature is testing the effect of COVID-19 on electricity demand by considering trade and GDP for the Visegrad countries. Our empirical findings show that there is no long-term causal relationship among these variables for the Visegrad countries. But, on the other hand, even if the trade variable is not significant in the long run, it is significant in the short run and for the cross-section models as it concerns the policy implications stemming from this exceptional and unique situation. We learned that it is difficult to frame any viable policy implications from such an extraordinary situation when many states have not tested their ad hoc measures. The best way, we consider, would be to renew trade and improve production before the next crisis. Nonetheless, in the area of technology, this painful period brought faster digitalization in all segments and the rationing of natural resources.